NLRP3 Inflammasome and Inflammatory Response in Aging Disorders: The Entanglement of Redox Modulation in Different Outcomes - Bhavana Chhunchha; Eri Kubo; Deepali Lehri; Dhirendra P. Singh (Cells, 2025)
Increasing evidence reveals that the deregulation of cellular antioxidant response with advancing age, resulting in the continuing amplification of oxidative stress-induced inflammatory response, is a pre-eminent cause for the onset of aging-related disease states, including blinding diseases. However, several safeguards, like an antioxidant defense system, are genetically in place to maintain redox homeostasis. Nonetheless, if the homeostatic capacity of such systems fails (like in aging), an inflammatory pathway elicited by excessive oxidative stress-evoked aberrant NLRP3 (NOD, LRR- and pyrin domain-containing protein 3) inflammasome activation can become pathogenic and lead to disease states. Among all known inflammasomes, NLRP3 is the most studied and acts as an intracellular sensor to detect danger(s). Upon activation, NLRP3 recruits apoptosis-associated speck-like protein containing a CARD (ASC) oligomerization and facilitates the recruitment of activated Caspase-1 (Cas-1), which results in the release of inflammatory cytokines, IL-1β and IL-18 and the activation of GasderminD, an executor of pyroptosis. NLRP3 inflammasome is tightly regulated in favor of cell health. However, when and how the activation of NLRP3 and its inflammatory components goes awry, leading to cellular derangement, and what regulatory factors are involved in the normal physiological and aging/oxidative conditions will be included in this review. Also, we address the latest findings to highlight the connection between oxidative stress, antioxidants, and NLRP3 activation as this begets aging diseases and explore the cellular pathways that are in place to regulate oxidative-induced inflammations and the pathobiological consequences of dysregulated inflammatory responses and vice versa.